Techno-economic assessment of hydrogen application in cereal crop farming - Anthony, Katumwesigye; Hellström, Magnus; Spohr, Jonas (Frontiers in Energy Research, 2025)
The application of hydrogen in modern farming is transitioning from a conceptual idea to a practical reality, poised to meet future agricultural machinery requirements and transition goals. Increasing tensions between farmers and various institutions underscore the growing sensitivity around fossil fuel dependency in the agricultural sector, particularly in northern economies. This study investigates the economic feasibility of using decentralized hydrogen systems to fully replace fossil fuels in cereal crop farming across four agricultural zones. Specifically, it examines the economic viability of on-farm hydrogen production using electrolysers to meet the fuel needs of different farm structures. Various scenarios were modelled to assess the impact of switching to hydrogen fuel for annual farm operations, using Net Present Value (NPV) and Levelized Cost of Hydrogen (LCOH) metrics for hydrogen refuelling facilities on distinct farm structures. The results indicate that economic feasibility is a significant challenge, with LCOH reaching as high as 57 €/kg of hydrogen in some cases, while the best-case scenarios achieved LCOH as low as 7.5 €/kg. These figures remain significantly higher than those for diesel and alternative fuels such as methane, FAME, and HVO. The study also assessed strategies for reducing hydrogen production costs using low-cost electricity and maximizing plant efficiency by increasing the electrolyser utilization rate to 70%. Additionally, the potential for revenue generation through the sale of by-products was explored. Our findings highlight both the challenges and opportunities associated with hydrogen use in agriculture, emphasizing the critical role of access to renewable energy sources and the economic limitations of by-product revenue streams. In conclusion, while decentralized hydrogen production can contribute to emission reductions in cereal crop farming, further research and policy support are essential to improve its feasibility and sustainability.